Neurobehavioral conditions and effects of gender, weight and severity in preterm infants according to the Neonatal Behavioral Assessment Scale. - Alicia Alvarez-Garcia (Anales de Psicología, 2015)
The increasing number of preterm babies in recent years has raised interest in studying the consequences of prematurity as a risk factor. In the present paper, 30 preterm babies (at 40 weeks of gestational age) were assessed using the Neonatal Beh avioral Asses s ment Scale and the r e- sults were compared with those of a control group of 28 full term babies. Moreover, the influence of weight, sex and gestational age was analyzed considering the Brazelton results in the preterm group. The preterm group s howed significantly lower scores than the co n trol group for 9 of the 28 behavioral items in the Scale and for 2 of the 5 clu s- ters. However, preterm babies performed better in habitu a tion to distur b- ing stimuli (light and noise) during sleep. In relation to the influence of sex, premature girls performed better in the Social - Interactive cluster. The preterm group has lower neurobehavioral conditions than the full term group, probably due to the abrupt interruption of their i n trauterine matur a- tion. In contrast , they showed a better ability of h a bituation, maybe as a consequence of a learning effect due to earlier additional extrauterine exp o- sition.